Gestión de inventarios en el Comisariato Jehová Jireh de la Parroquia Rural La Unión del cantón Babahoyo - Zambrano Egas, Kevin Andrés (2021)
The investigative process that was carried out explicitly consists of analyzing the deficient inventory management and thus being able to determine what are the different shortcomings that this problem generates, by obtaining data it was established that the hiring of a person who is in charge of carrying out the process is lacking. of control in the warehouse area, this as a consequence generates a lack of inventory rotation, for which the inventory tends to occupy spaces for long periods of time as well as deteriorate, losing its value, for such reasons there are economic losses for the commercial. In matters of the internal labor environment, it was determined that there is a lack of training for employees on relevant topics such as customer service, logistics, among others. The constant rotation of collaborators is another of the main causes of the different problems that arise due to low performance, as well as the little work commitment on the part of the personnel who work in this commissary.